Living on the land: indigenous women's understanding of place - Altamirano-Jiménez, Isabel; Kermoal, Nathalie J.; Horn-Miller, Kahente (AU Press, 2016)
From a variety of methodological perspectives, contributors to Living on the Land explore the nature and scope of Indigenous women's knowledge, its rootedness in relationships, both human and spiritual, and its inseparability from land and landscape.
Le texte de Horn Miller, Kahente (2016). Distortion and Healing: Finding Balance and a ‘Good Mind’ through the rearticulation of Sky Woman’s Journey, a été donné en lecture au cours POL4105.
Keywords: amériques; approches et analyses; canada; cours; cree; discipline; environnement; féminisme autochtone; histoire; métis; naskapi; nicaragua; pol4105; premier cycle; ressource en ligne; régions géographiques; sciences humaines; thématiques; études autochtones; île de la tortue

Gender differentials and old age survival in the Nairobi slums, Kenya - Bennett, Rachel; Chepngeno-Langat, Gloria; Evandrou, Maria; Falkingham, Jane (Social Science & Medicine, 2016)
This paper examines gender differentials in survival amongst older people (50+ years) in the Nairobi slums and to the best of our knowledge is the first study of its kind in an urban African setting. The results provide evidence contrary to the expected paradox of poorer self-rated health yet better survival amongst older women. Older women in the Nairobi slums have poorer self-rated health and poorer circumstances across other factors, including disability and socio-economic status. Further, older women in the slums do not have better survival. The conventional female advantage in mortality only becomes apparent after accounting for the cumulative influence of individual characteristics, social networks, health and socio-economic status, suggesting the female advantage in unadjusted old-age mortality does not apply to contexts where women experience significant disadvantage across multiple life domains. This highlights the urgent need to redress the support, status and opportunities available for women across the life course in contexts such as the Nairobi slums. In addition, a greater number of factors differentiate mortality risk amongst men than amongst women, suggesting inequality amongst slum dwelling older men and highlighting the need for gender sensitive interventions which account for the particular needs of both genders in old age.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; bidonvilles; environnement; inégalités; kenya; personnes âgées; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques

Glaciers, gender, and science: A feminist glaciology framework for global environmental change research - Carey, Mark; Jackson, M.; Antonello, Alessandro; Rushing, Jaclyn (Progress in Human Geography, 2016)
Glaciers are key icons of climate change and global environmental change. However, the relationships among gender, science, and glaciers – particularly related to epistemological questions about the production of glaciological knowledge – remain understudied. This paper thus proposes a feminist glaciology framework with four key components: 1) knowledge producers; (2) gendered science and knowledge; (3) systems of scientific domination; and (4) alternative representations of glaciers. Merging feminist postcolonial science studies and feminist political ecology, the feminist glaciology framework generates robust analysis of gender, power, and epistemologies in dynamic social-ecological systems, thereby leading to more just and equitable science and human-ice interactions.
Keywords: approches et analyses; discipline; environnement; glaciologie; histoire et politique; intersectionnalité; point de vue situé; projet charge mentale; sciences; sciences de la terre; thématiques; études postcoloniales

Genre et changements climatiques : analyse de la vulnérabilité à partir des rapports sociaux de sexe - Gramme, Sophie (Université du Québec à Montréal, 2016)
Avec cette recherche, nous nous proposons de questionner les liens entre genre et changements climatiques dans les pays occidentaux. Partant d'un corpus de texte constitué à partir d'une recherche bibliographique conduite durant l'été 2011, et réunissant des auteures qui travaillent comment réaliser une analyse genrée des changements climatiques dans les pays occidentaux, nous avons interrogé les définitions du genre utilisées et comment ces utilisations produisaient un discours sur les liens entre le genre et les changements climatiques qui nous semblait questionnable. Au cœur de ce travail est donc la mise en lumière d'un certain discours sur les liens entre le genre et les changements climatiques, celui de la vulnérabilité. Ne nous satisfaisant pas d'une analyse féministe dont l'argument premier mis de l'avant pour justifier sa pertinence est celui de la vulnérabilité, nous avons mis au centre de nos questionnements les choix méthodologiques qui amènent à la production d'un tel discours sur les femmes et les changements climatiques. Notre contenu de recherche s'est concentré sur une exploration historique de l'articulation du genre et de l'environnement, une mise en discussion à partir des théories féministes de l'usage du genre au regard du concept de rapports sociaux de sexe, et un ancrage dans le corpus étudié qui offre un aperçu du paysage de recherche sur le genre et les changements climatiques dans les pays occidentaux. Nous nous proposons de réfléchir sur l'homogénéité des discours émergeant de cette recherche, et explorons les diverses implications de la production d'observations monolithiques sur la plus grande vulnérabilité des femmes face aux changements climatiques due à leur pauvreté et la plus grande responsabilité des hommes pour leurs habitudes de consommation et de transports émettrices de C02• Prenant d'assaut ces affirmations, nous en produisons une lecture critique ancrée dans notre compréhension du projet scientifique de production de connaissances et du projet socio-politique de la recherche féministe par la contribution à une transformation des rapports sociaux de sexe.
Keywords: approches et analyses; discipline; environnement; féminisme matérialiste; projet charge mentale; rapports sociaux de sexe; sciences; sciences de l'environnement; thématiques

Amun: nouvelles - Jean, Michel (Stanké, une société de Québecor média, 2016)
« Dans la langue innue, amun signifie « rassemblement ». Sous la direction de Michel Jean, écrivain et journaliste innu, ce collectif brûlant d'actualité réunit des auteurs autochtones de divers horizons, de différentes nations et générations. Leurs nouvelles, variées, reflètent non seulement l'histoire et les traditions, mais aussi la réalité des Premières Nations au Québec et au Canada. Offrant à lire les points de vue d'artistes de renom, ce livre est le théâtre d'un rassemblement qui ne se fait que trop rarement. »–Quatrième de couverture.
Les nouvelles de Fontaine, Natacha Kanapé, 2016. « J’ai brûlé toutes les lettres de mon prénom » et de Cousineau-Mollen, Maya, 2016. « Mitatamun (Regret) » ont été données en lecture au cours SEX2283
Keywords: amériques; appartenance; approches et analyses; arts; canada; cours; discipline; environnement; féminisme autochtone; littérature; littérature autochtone; pensionnats; premier cycle; premières nations; québec; racisme; régions géographiques; sex2283; spiritualité; système colonial; systèmes d'oppressions; thématiques; violences; études littéraires

Agir avec le désespoir environnemental - Macy, Joanna (Reclaim : recueil de textes écoféministes, 2016)
Keywords: EDI; amériques; approches et analyses; cours; discours dominant; environnement; fem1000; fem3600; justice sociale; mouvements sociaux; pratiques féministes; premier cycle; régions géographiques; systèmes d'oppressions; thématiques; écoféminisme; écopsychologie; états-unis

Leading in disadvantaged Zimbabwean school contexts: Female school heads’ experiences of emotional labour - Zikhali, Joyce; Perumal, Juliet (Educational Management Administration and Leadership, 2016)
This qualitative multiple case study explored the sources of emotional stress experienced by 12 female Zimbabwean primary heads leading in socio-economic disadvantaged schools in Masvingo District and their attempts to alleviate the challenges that the children from these disadvantaged contexts presented them with. Data was generated through individual semi-structured interviews, and observations and the data was analysed thematically to elicit the sources of their emotional labour that emanated from stress-related cultural and contextual factors. The study revealed that despite the school heads experiencing anxiety, pain, sorrow, sympathy, frustration, sadness, and concern they were happy about their appointments to leadership positions. The sources of their emotional stress were related to the plight of children; stereotypical gender expectations; lack of parental cooperation; and unrealistic professional and social expectations. The study suggests wellness recesses; the establishment of social networks through which heads could share their experiences; and professional development programmes on stress management as possible interventions that could help the heads deal with these stressful circumstances. © 2015, © The Author(s) 2015.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; directrices d'école; enfants orphelins; environnement; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail; travail émotionnel; zimbabwe; éducation